KEPEMIMPINAN LEMBAGA PEMASYARAKATAN : GAYA KEPEMIMPINAN DAN PEMBERIAN MOTIVASI MEMPENGARUHI KEPUASAN KERJA PETUGAS PEMASYARAKATAN - Agung Tri Sakti; Ali Muhammad (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
The aims and objectives of this research are to test the level of authority leadership, motivation, commitment of an organization, intelligence and compliance with the ethics of correctional officers. Studying the effects of leadership on authority, motivation, organizational commitment and intelligence on compliance with applicable regulations. Achieving the goals of an organization is also due to leaders who are able to commit to always advancing the organization they lead, especially by providing motivation to improve the quality of work of its members. Therefore, it is necessary for leaders to instill motivation and direct involvement in the field in order to know the actual situation and the need for the ability to think and learn what influences the performance of correctional officers in the field. The method used in this research is literature study by analyzing and searching articles or previous research. With high motivation, employees consider the importance of whatever work they undertake so that employees will automatically show discipline in carrying out or completing their work. Therefore, leadership has a positive and significant effect on organizational participation. The better the leadership of the head of the correctional institution (Kalapas), the higher the organizational commitment of the correctional institution. The creation of a work commitment also of course requires support based on its members who are always serious and focused on one goal, namely to advance the organization, specifically in this case the correctional organization.